(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this study, the effect of the weighted expert factor on time fuzzy soft expert sets (W-TFSES) is introduced as an extension of the fuzzy soft set. We will also define and investigate the features of its main operations (complement, union, intersection, AND, and OR). Finally, we will apply this approach to decision-making difficulties.